U‐shaped association between serum IGF2BP3 and T2DM: A cross‐sectional study in Chinese population. Issue 4 (9th March 2023) - Wu, Xiaoying; Wang, Wei; Fan, Shujin; You, Lili; Li, Feng; Zhang, Xiaoyun; Wu, Hongshi; Tang, Juying; Qi, Yiqin; Feng, Wanting; Yan, Li; Ren, Meng
Abstract: Objective: To clarify the expression of N6‐methyladenosine (m 6 A) modulators involved in the pathogenesis of type 2 diabetes mellitus (T2DM). We further explored the association of serum insulin‐like growth factor 2 mRNA‐binding proteins 3 (IGF2BP3) levels and odds of T2DM in a high‐risk population. Methods: The gene expression data set GSE25724 was obtained from the Gene Expression Omnibus, and a cluster heatmap was generated by using the R package ComplexHeatmap. Differential expression analysis for 13 m 6 A RNA methylation regulators between nondiabetic controls and T2DM subjects was performed using an unpaired t test. A cross‐sectional design, including 393 subjects (131 patients with newly diagnosed T2DM, 131 age‐ and sex‐matched subjects with prediabetes, and 131 healthy controls), was carried out. The associations between serum IGF2BP3 concentrations and T2DM were modeled by restricted cubic spline and logistic regression models. Results: Two upregulated (IGF2BP2 and IGF2BP3) and 5 downregulated (methyltransferase‐like 3 [METTL3], alkylation repair homolog protein 1 [ALKBH1], YTH domain family 2 [YTHDF2], YTHDF3, and heterogeneous nuclear ribonucleoprotein [HNRNPC]) m 6 A‐related genes were found in islet samples of T2DM patients. A U‐shaped association existed between serum IGF2BP3 levels and odds of T2DM according to cubic natural spline analysis models, after adjustment for body mass index, waist circumference, diastolic blood pressure, total cholesterol, and triglyeride. Multivariate logistic regression showed that progressively higher odds of T2DM were observed when serum IGF2BP3 levels were below 0.62 ng/mL (odds ratio 3.03 [95% confidence interval 1.23–7.47]) in model 4. Conclusion: Seven significantly altered m 6 A RNA methylation genes were identified in T2DM. There was a U‐shaped association between serum IGF2BP3 levels and odds of T2DM in the general Chinese adult population. This study provides important evidence for further examination of the role of m 6 A RNA methylation, especially serum IGF2BP3 in T2DM risk assessment. Abstract : Highlights This is the first cross‐sectional study of the association between serum IGF2BP3 levels and odds of T2DM in high‐risk Chinese population. Two upregulated (IGF2BP2 and IGF2BP3) and 5 downregulated (METTL3, ALKBH1, YTHDF2, YTHDF3, and HNRNPC) m 6 A‐related genes could contribute to the occurrence of T2DM. A U‐shaped association existed between serum IGF2BP3 levels and odds of T2DM, which highlights diagnostic and prognostic values of serum IGF2BP3 in T2DM risk assessment. 摘要: 目的: 探讨N6 ‐甲基腺苷(m 6 A)调节因子在2型糖尿病(T2DM)发病机制中的表达。我们进一步探索血清胰岛素样生长因子2 mRNA结合蛋白3 (IGF2BP3)水平与高危人群T2DM发病风险的关系。 方法: 从基因表达综合数据库获得基因表达数据集GSE25724, 使用R包ComplexHeatmap生成聚类热图。采用非配对T检验分析13个m 6 A RNA甲基化调控因子在非糖尿病对照者和T2DM受试者之间的差异表达。本研究为横断面研究, 共纳入393例研究对象, 其中新诊断T2DM患者131例, 年龄、性别相匹配的糖尿病前期患者131例, 健康对照者131例。采用限制性立方样条和logistic回归模型分析血清IGF2BP3浓度与T2DM的关系。 结果: 在T2DM患者胰岛中发现2个上调的m 6 A相关基因(IGF2BP2和IGF2BP3)和5个下调的m 6 A相关基因(METTL3、ALKBH1、YTHDF2、YTHDF3和HNRNPC)。校正BMI、腰围、舒张压、总胆固醇和三酰甘油后, 三次自然样条模型显示血清IGF2BP3水平与T2DM患病风险呈U型曲线关系。多因素logistic回归模型4显示, 当血清IGF2BP3水平低于0.62 ng/ml时, T2DM的发病风险逐渐增加[OR 3.03 (95% CI 1.23 ~ 7.47)]。 结论: T2DM患者存在7个m 6 A RNA甲基化基因的显著改变。中国成年人血清IGF2BP3水平与T2DM发病风险之间存在U型关联。本研究为进一步探讨m 6 A RNA甲基化尤其是血清IGF2BP3在T2DM风险评估中的作用提供了重要依据。